Literature Review Traditional Medicine To Stabilize Blood Pressure In Hypertension Sufferers - Riska Nabila; Hidiyatul Fithi (MultiTech Publisher, 2023)
Hypertension occurs when blood pressure exceeds normal limits, with a systolic pressure typically around 140 mmHg and a diastolic pressure around 90 mmHg. One approach to managing blood pressure involves a combination of modern therapies and the utilization of traditional herbal remedies. This study is a literature review aimed at gathering data and sources related to a specific topic from various sources, including journals, books, the internet, and other published works. Several herbal plants, such as dates, boiled celery water, moringa leaves, papaya leaves, ginger, garlic extract, cucumber juice, and carrot juice, can serve as traditional remedies to lower blood pressure. Hypertensive patients may consider using traditional (non-pharmacological) medicine as an alternative for blood pressure reduction.